PEMBELAJARAN KOOPERATIF TIPE STAD MATERI MENYELESAIKAN MODEL MATEMATIKA DARI MASALAH YANG BERKAITAN DENGAN PERSAMAAN LINIER SATU VARIABEL - Faridah, Luluk (Jurnal Ilmiah AdMathEdu, 2012)
One of the learning model used is the direct teaching of teachers. In this model teachers usually to used traditional lecture method with little questioning and accompanied by the assignment, so that the teacher is not giving the opportunity for students to interact and cooperate with others. As a result of this study pretended to be one way, it is means that the teachers provides information or ideas, and students take it for granted. Such a learning model does not involve students actively. Many problems in daily life that can be expressed in mathematical form of the sentence. With the sentence of the problem or idea of mathematics more practical, systematic and efficient to communicated and solve. However, based on observation and discussion researcher and many mathematics teachers SMPN 3 Taman was still a lot of students who have difficulty in completing the topic. This research is descriptive research that describes or explains the event. The research is done at SMPN 3 Taman Sidoarjo and the subject of the research is students of class VII B. The purpose of this research is to describe the students result, students activities and students response to cooperative learning STAD type. Based on data analysis, it is known to students learning completeness is 81,58 %. This shows that classically students learning is complete. Students activities during teaching-learning can be said active with average percentage of activity by 86,06 %, Students give positive response to the average percentage of 86,842 %.